Electrochemistry of thin film electrodes via surface modification - Tham, Guo Xiong (Nanyang Technological University, 2020)
Surface modification of electrodes is an experimental method commonly used in electroanalytical chemistry. The thesis focused on three major areas that involved the surface modification of glassy carbon (GC) electrodes. In the first part of the thesis, a vitamin-based voltammetric pH sensor was developed with the drop cast of riboflavin (VB2) and a vitamin E analogue (VEa) as the pH-sensitive and pH-insensitive redox active compounds, respectively, on the GC electrode surface. Nernstian responses were observed in deoxygenated and oxygenated buffered media at pH 1–11, and in deoxygenated and oxygenated unbuffered media with the addition of a very small concentration of acidic buffer. In the second part of the thesis, the dispersion of the functionalised carbon nanotubes was utilised with various solvents and drop cast onto GC electrode surfaces. Different classes of surfactants with varying concentrations were also used in the bulk solution to test the cyclic voltammograms of the immersed film electrodes. The analysis of the electrode kinetics was built on and verified with the combination of thin layer diffusion and semi-infinite diffusion via interpretation of the current responses of the modified electrodes. Finally, the last part of the thesis covers the electrochemical energy storage capability of the electrochemically co-polymerised PANIMEL/fMWCNT/GCE film electrode. Various factors were explored in the electrosynthesis of individual monomers prior to the electrochemical co-polymerisation. A series of electrochemical tests pertaining to the electrochemical cyclability and stability of the co-polymeric film were performed with a view of stabilizing the daughter polymeric melamine in the co-polymerised film to optimize the capacitor properties.